Optimization of Medium Composition for Streptomyces sp. PB2 Chitinase Production using Response Surface Methodology - Anandita Perwita Kurniawan; Indun Dewi Puspita; Amir Husni (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight ResearchThe chitinase production by Streptomyces sp. PB2 was studiedThe critical medium component for chitinase production were identifiedThe optimum medium composition for chitinase production was obtainedMedium optimization improved chitinase production by 6-fold increase in activityAbstractChitin is a polysaccharide compound composed of N-acetylglucosamine (NAG), which is linked by β-1,4-glycoside bonds. In producing NAG from chitin, enzymatic method using chitinase offer advantages compared to chemical degradation. Streptomyces sp. PB2 is a good candidate of chitinase producer which was previously isolated from shrimp pond sediment. However, optimization of chitinase production by Streptomyces sp. PB2 is required for large-scale production of this enzyme. This study aimed to find the optimal medium composition to increase the chitinase enzyme activity of Streptomyces sp. PB2 using the Response Surface Method. Initial screening was done to determine additional carbon and nitrogen sources in colloidal chitin broth suitable for increasing chitinase activity. Optimization of the medium composition was conducted using the Plackett-Burman design to determine the critical components in the colloidal chitin broth medium and continued by Box-Behnken model to optimize the concentration of the medium components. Chitinase activity was obtained by measuring the amount of reducing sugar (NAG) released from enzymatic reaction using DMAB reagent by means of spectrophotometer. The medium components showing high contribution in increasing chitinase activity were K2HPO4, colloidal chitin and peptone, with the confidence level value of 0.66, 0.48, and 0.38, respectively. The Box-Behnken model analysis shows that the combination of K2HPO4 0.007 g/ml, colloidal chitin 1.5 g/ml and peptone 1.5 g/ml in colloidal chitin broth are the optimal medium for Streptomyces sp. PB2, resulted in chitinase activity of 0.0125 U/ml. The increase of 6-fold in chitinase activity was achieved in this study.